Alih Fungsi Pemanfaatan Lahan Di Desa Karawana Kecamatan Dolo Kabupaten Sigi - Mutmainnah Patimbuk; Harnida Wahyuni Adda; Ni Made Suwitri Parwati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The use of farmers' land in Karawana Village is a breakthrough that really helps farmers in increasing income. This community service activity aims to determine the transition of the function of the farmers' land from paddy fields to corn and tomato plants in Karawana Village, which is very helpful for farmers because after the earthquake and liquefaction resulted in total damage to irrigation canals which hampered the irrigation process to the rice fields. Therefore, the farmers approached the government and were given alkon tools (water suction machines) and the construction of artificial wells so that it really helped farmers, especially corn and tomato farmers, then regarding marketing management of the corn and tomato crops the farmers were able to manage. . This is very helpful in the process of increasing the income of farmers in Karawana Village